(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Ioana-Mădălina Iftime explores the carnivalesque Hell in François Rabelais's work, applying Lyotard’s concept of postmodern paralogy. The study analyzes how Rabelais delegitimizes medieval hierarchies and the fear of death through laughter, the grotesque, and hyperbole. In this Rabelaisian vision, Hell becomes a democratic, fertile space where historical figures receive inverted roles. Epistemon’s resurrection symbolizes the victory of vital force and human physiology over nothingness, transforming Christian negation into an ontology of affirmation. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.